When is Migration Voluntary?1. Issue 4 (December 2013) - Ottonelli, Valeria; Torresi, Tiziana
<x xml:space="preserve">Abstract</x> In this paper we critically evaluate the role that the notion of voluntariness plays in the normative theory of migration. We argue that the notion is currently underdefined and works to undermine migrants' claims to see their migratory projects properly recognized. We argue that it is nevertheless important to be able to define when migration can be said to be voluntary if we are to theorize appropriate normative and policy responses to migrants' claims. We propose therefore a series of sufficient and necessary conditions to the definition of voluntary migration. We use the case of temporary migration to illustrate our argument.